2022
DOI: 10.1186/s12870-022-03564-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression of SAUR gene family in peanut (Arachis hypogaea L.) and functional identification of AhSAUR3 in drought tolerance

Abstract: Background Small auxin-upregulated RNAs (SAURs) gene family plays important roles in plant growth, development, and stress responses. However, the function of few SAUR genes is known in the peanut (Arachis hypogaea L.), one of the world’s major food legume crops. This study aimed to perform a comprehensive identification of the SAUR gene family from the peanut genome. Results The genome-wide analysis revealed that a total of 162 SAUR genes were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Specifically, 22 different transcriptome samples were obtained from Genbank BioProject PRJNA291488 [ 71 ]. Transcriptome assembly and expression value estimation (Fragments per kilobase million, FPKM) were performed using StringTie (v1.3.4) with default parameters, as reported by Liu et al [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 22 different transcriptome samples were obtained from Genbank BioProject PRJNA291488 [ 71 ]. Transcriptome assembly and expression value estimation (Fragments per kilobase million, FPKM) were performed using StringTie (v1.3.4) with default parameters, as reported by Liu et al [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specific primers were designed using Beacon Designer 7.0 software ( Table S1 ). The housekeeping gene TUA5 was used as an internal reference with primers, as described by Liu et al [ 72 ]. RT-qPCR was performed using a HiScript III RT SuperMix kit (Vazyme, Nanjing, China), as described by Lu et al [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the expression of SAURs is induced by exogenous auxin. Liu et al (2022) report that AhSAURs from different subfamilies exhibit distinct expression characteristics in response to IAA. Notably, the expression levels of most members in subfamily II and subfamily III are up-regulated and peak after 30 minutes of IAA treatment in A. hypogaea.…”
Section: Disscussionmentioning
confidence: 99%
“…Interestingly, the chromosomal distributions of the SAUR gene family in the genomes of other higher plant species, such as coffea [19], melon [21], and wax gourd [23] also confirmed our finding. Previously, the SAUR family is being explored in various higher plant species, such as potato [12], tomato [12], watermelon [13], cotton [14], moso bamboo [15], poplar [16], grape [17], apple [18], coffea [19], Chinese white pear [20], melon [21], loquat [22], wax gourd [23], peanut [24], pineapple [25], foxtail millet [26], cucumber [27], and longan [28]. More specifically, 31 and 38 members of the SAUR families have been recorded in coffea and moso bamboo [15,19].…”
Section: Identification and Annotation Of Tcsaur Genes In Cacaomentioning
confidence: 99%
“…To gain an insight into their functions, previous studies have been performed to analyze the SAUR families in many important crop species, including potato (Solanum tuberosum) and tomato (Solanum lycopersicum) [12], watermelon (Citrullus lanatus) [13], cotton (Gossypium spp.) [14], moso bamboo (Phyllostachys edulis) [15], poplar (Populus trichocarpa) [16], grape (Vitis vinifera) [17], apple (Malus domestica) [18], coffea (Coffea canephora) [19], Chinese white pear (Pyrus bretschneideri) [20], melon (Cucumis melo) [21], loquat (Eriobotrya japonica) [22], wax gourd (Benincasa hispida) [23], peanut (Arachis hypogaea) [24], pineapple (Ananas comosus) [25], foxtail millet (Setaria italica) [26], cucumber (Cucumis sativus) [27], and longan (Dimocarpus longan) [28]. However, this important gene family in cacao has not been recorded, even though the assembly of cacao was released [29].…”
Section: Introductionmentioning
confidence: 99%